Participatory Variety Selection and Promotion of Improved Soybean (Glycine max L.) Variety in Northwestern Ethiopia - Zeleke, Bantalem; Esmeal, Jemal; Abebe, Dereje; Mengie, Yitayal (Journal of Tropical Crop Science, 2025)
A participatory variety selection (PVS) approach was used to evaluate the varieties when selecting new soybean varieties. Farmers were requested to state the most important traits when deciding which soybean varieties to adopt. The study aimed to identify a high-yielding variety that fulfills farmers’ preferences, creates wider demand, and strengthens linkage among the possible actors in improved soybean varieties. The study was conducted at Jawe, Guangua, and North Achefer locations in the Awi and West Gojam zones during the 2018 and 2019 cropping seasons. Eight improved soybean varieties were considered in the experiment. Farmers identified seven biological attributes as their selection criteria and considered social factors when deciding which variety to grow. High grain yields of 1830 kg.ha-1 and 1680 kg.ha-1 were recorded for varieties “Pawe-02” and “Wegayen,” respectively, whereas the lowest grain yield of 1430 kg.ha-1 was recorded for the variety “Ethio-Yugoslavia.” “Pawe-02” variety was ranked 1st by farmers’ selection in two districts among the eight varieties. The average performance of the “Pawe-02” variety in the pre-scale-up activity was 2580 kg.ha-1 with a yield advantage of 48.87%. Likert-scale analysis indicated that farmers positively perceived the important traits “Pawe-02” against the existing soya bean variety. Therefore, the “Pawe-02” variety should be recommended to farmers on a large scale to benefit them in this study area and similar agroecology.